Development of Problem Solving-Based Modules Assisted by Tracker Software to Improve Students' Problem-Solving Skills in High School - Istiqomah, Santi; Lubis, Patricia H. M; Lefudin, Lefudin (Universitas Muhammadiyah Makassar, 2023)
This study aims to 1) produce problem solving-based modules assisted by software tracker to improve valid problem-solving abilities; 2) produce problem solving based modules assisted by tracking software to improve practical problem solving skills; 3) find out the potential effects of problem solving-based modules assisted by tracker software to improve students’ problem solving skills. This study used research and development (R&D) methods which refer to the ADDIE development procedure. includes Analysis, Design, Development, Implementation, Evaluation. One of the ADDIE's stages is modifying the development stage using Tessmer's evaluation. If it consists of self-evaluation, expert review, one to one, and small group. Data collection was carried out by observation, interviews, questionnaires/questions. The research subjects were class X IPA students at SMA Negeri 3 Sungai Lilin. Based on the analysis, the data is stated to be valid, practical and has the potential to influence students. The results obtained 1) The expert review stage showed the average value from the three experts, namely 91.11% for material aspects, 93.33% for media aspects, and 81.11% for language aspects. 2) The one-to-one stage has a percentage value of 84.44 % which is categorized as practical. 3) The small group students’ response questionnaire has a score percentage of 87.778% which is categorized as practical. and 4) the field test stage shows an average value of 44 .2563 in the pretest and 83.9063 in the post-test. Therefore, it can be concluded that the problem solving-based module assisted by tracker software can be stated as valid, practical, and effective to improve students’ problem-solving skills.